Analysis of Plain and Threaded Spiral Reinforcement on The Compressive Strength of Concrete Cylinder with Coarse Agregate From Baula - Mursalim La Ola; Fathur Rahman Rustan; Arman Hidayat; Nira Niza (Universitas Medan Area, 2023)
Column is a part of concrete structure that bears the largest axial compressive load. The use of stirrup reinforcement in columns can maintain strength and stability so that the load is distributed evenly. The Indonesian Structural Concrete Requirements for Building (SNI 2847:2019) requires the use of threaded steel bar in column structures. This research aims to determine the effect of using plain steel bars (BJTP) and threaded steel bars (BJTS) reinforcement with a spacing variation of 3 cm and 5 cm. The research was conducted by conducting cylinder concrete test with a diameter of 15 cm and a height of 30 cm, spiral reinforcement with a diameter of 10 cm, concrete cover of 25 mm, and plain and threaded steel bars with a diameter of 10 mm. The test object is divided into 5 conditions, namely without any reinforcement, plain steel bars reinforcement, threaded steel bars reinforcement, and variations of 3 cm and 5 cm spacing on each steel bar reinforcement. The concrete used is made of local materials Baula splits and Tamboli sands from Kolaka District. The test results on concrete at 28 days showed that the use of spiral reinforcement on cylinder concrete can significantly increase its compressive strength by more than 50%, even reaching above 100% at closer spacing. Spiral reinforcement with threaded steel bars shows better strength increase compared to spiral reinforcement with plain steel bars.